Diagnostic approach to occupational rhinitis: the role of nasal provocation tests. Issue 2 (April 2020) - Ronsmans, Steven; Steelant, Brecht; Backaert, Wout; Nemery, Benoit; Van Gerven, Laura
Abstract : Purpose of review: The diagnosis of occupational rhinitis is a challenge. Underdiagnosis is substantial as the clinical presentation is nonspecific and often no occupational history is taken. Detection of occupational rhinitis can be improved by including screening questions on occupational exposure in the assessment of every patient with adult-onset rhinitis. Recent findings: Case reports, case series and epidemiological studies continuously demonstrate new sensitizers and irritants capable of inducing allergic or nonallergic (irritant-induced) occupational rhinitis. Recent reviews have focused on the value of immunological tests with specific IgE, skin prick tests or basophil activation tests in demonstrating sensitization to occupational agents. Nasal provocation tests (NPT) can establish a definite diagnosis of allergic occupational rhinitis. Several NPT guidelines have been published, however, focusing exclusively on standardized high-molecular weight allergens. When performing NPT with nonstandardized agents – like most occupational sensitizers – adapted protocols are needed. Summary: We provide pragmatic guidance to clinicians taking care of rhinitis patients on how to diagnose occupational rhinitis, based on recent insights from the literature. We focus on the challenges in the diagnostic work-up, on how to identify suspected causes, and on the role of NPT.